+0  
 
0
227
1
avatar

(X^-2 +X^-1)÷(X+X^-3)

Guest May 13, 2015

Best Answer 

 #1
avatar+91038 
+5

$$\\(X^{-2} +X^{-1})\div(X+X^{-3})\\\\
=(\frac{1}{X^{2}} +\frac{1}{X^{1}})\div(X+\frac{1}{X^{3}})\\\\
=\frac{1+X}{X^{2}} \div\frac{X^4+1}{X^{3}}\\\\
=\frac{1+X}{X^{2}} \times \frac{X^{3}}{X^4+1}\\\\
=\frac{1+X}{1} \times \frac{X}{X^4+1}\\\\
= \frac{X(X+1)}{X^4+1}\\\\$$

Melody  May 14, 2015
Sort: 

1+0 Answers

 #1
avatar+91038 
+5
Best Answer

$$\\(X^{-2} +X^{-1})\div(X+X^{-3})\\\\
=(\frac{1}{X^{2}} +\frac{1}{X^{1}})\div(X+\frac{1}{X^{3}})\\\\
=\frac{1+X}{X^{2}} \div\frac{X^4+1}{X^{3}}\\\\
=\frac{1+X}{X^{2}} \times \frac{X^{3}}{X^4+1}\\\\
=\frac{1+X}{1} \times \frac{X}{X^4+1}\\\\
= \frac{X(X+1)}{X^4+1}\\\\$$

Melody  May 14, 2015

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details